Rhinolith - Patil Karthikeya; Guledgud Mahima; Malleshi Suchetha (Indian Journal of Dental Research, 2009)
Rhinoliths are rare entities encountered in clinical practice. They are calcified masses found within the nasal cavity. Which lesions can be encountered incidentally upon a routine dental radiograph. This article reports a case of such an incidental finding of rhinolith on a dental radiograph.